Development and Application of Internal Circulating Water-cooled Electromagnetic Separator. Issue 1 (1st January 2022) - Lu, Juan; Yan, Xiaolei; Du, Bin; Lu, Jing
Abstract: For dusty and explosive use environment, especially in coal mines, mostly self-cooled and water-cooled electromagnetic iron separators are used. This article introduces the application of water cooling internal circulation technology to electromagnetic separator equipment for the first time, the advantages and disadvantages of the three cooling methods as well as the development process and application prospects of the internal circulating water-cooled electromagnetic separator are introduced and analyzed respectively.